Patterns of innovative outputs across climate zones: the geography of innovation. (1st June 2015) - Coccia, Mario
Abstract : Technological innovation is a vital human activity that interacts with geographic factors and the natural environment. The purpose of the present study is to explain the relationship between climate zones and innovative outputs in order to detect factors that can spur technological change and, as a consequence, human development. The findings show that innovative outputs are high in geographical areas with temperate climate. In effect, warm temperate climates are an appropriate natural environment for humans that, by an evolutionary process of adaptation and learning, create complex societies, efficient institutions and communications systems. This socio-economic platform supports the efficient use of human capital and assets that induce inventions, innovations and their diffusion.